Specifics of thermal transport in graphene composites: effect of lateral dimensions of graphene fillers - Sudhindra, Sriharsha; Rashvand, Farnia; Wright, Dylan; Barani, Zahra; Drozdov, Aleksey D.; Baraghani, Saba; Backes, Claudia; Kargar, Fariborz; Balandin, Alexander A. (ACS applied materials & interfaces, 2021)
We report on the investigation of thermal transport in noncured silicone composites with graphene fillers of different lateral dimensions. Graphene fillers are comprised of few-layer graphene flakes with lateral sizes in the range from 400 to 1200 nm and the number of atomic planes from 1 to ∼100. The distribution of the lateral dimensions and thicknesses of graphene fillers has been determined via atomic force microscopy statistics. It was found that in the examined range of the lateral dimensions, the thermal conductivity of the composites increases with increasing size of the graphene fillers. The observed difference in thermal properties can be related to the average gray phonon mean free path in graphene, which has been estimated to be around ∼800 nm at room temperature. The thermal contact resistance of composites with graphene fillers of 1200 nm lateral dimensions was also smaller than that of composites with graphene fillers of 400 nm lateral dimensions. The effects of the filler loading fraction and the filler size on the thermal conductivity of the composites were rationalized within the Kanari model. The obtained results are important for the optimization of graphene fillers for applications in thermal interface materials for heat removal from high-power-density electronics.